(untitled) (American Journal of Research in Humanities and Social Sciences, 2024)
This article focuses on stylistic changes in the example of Daniel Defoe’s The Life and Adventures of Robinson Crusoe. Examples given in two languages throughout the article allow understanding the new types of stylistic transformation.